2007
DOI: 10.1111/j.1432-2277.2007.00460.x
|View full text |Cite
|
Sign up to set email alerts
|

Role and significance of plasma citrulline in the early phase after small bowel transplantation in pigs

Abstract: Summary A reliable serological marker of acute cellular rejection (ACR) after small bowel transplantation (SBTx) is still missing. Plasma citrulline level (PCL) reflects the functional integrity of intestinal mucosa which is partially lost during ACR. The aim of our study was to investigate the role of PCL as marker of ACR after SBTx. Eighteen German landrace pigs were used and divided into three groups. Group 1 (G1), autologous SBTx (n = 4) as control; group 2 (G2), allogeneic SBTx without immunosuppression (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 31 publications
(41 reference statements)
0
17
0
Order By: Relevance
“…Recently, in Nadalin's experimental study, the results suggested that measurement of the plasma citrulline level could be useful as a marker of rejection (Nadalin et al, 2007). However, the plasma level of citrulline was not sufficient for identifying a mild form of ACR in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in Nadalin's experimental study, the results suggested that measurement of the plasma citrulline level could be useful as a marker of rejection (Nadalin et al, 2007). However, the plasma level of citrulline was not sufficient for identifying a mild form of ACR in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Other forms of application [20,21] or no heparinization at all [11,17,22,23] have been reported as well. Both systemic [5, 10-12, 16, 21, 22, 24] perfusion and flushing of the bowel during back-table procedures [4,14,15,25] have been described. Systemic perfusion of the graft is mainly performed by cannulating the infrarenal aorta [5, 10-12, 16, 21, 22, 24].…”
Section: Small Bowel Graft Procurementmentioning
confidence: 99%
“…Systemic perfusion of the graft is mainly performed by cannulating the infrarenal aorta [5, 10-12, 16, 21, 22, 24]. In case of ex situ flushing, it is performed through the SMA [4,14,15,[24][25][26][27]. In most models, iced Lactated Ringers Solution [4,12,17,24,25,27] or University of Wisconsin Solution is used as perfusion solution [7,11,13].…”
Section: Small Bowel Graft Procurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most studies concerning intestinal reperfusion injury used in situ warm ischemia models, the results cannot be directly extrapolated to the reperfusion injury associated with intestinal transplantation, which consists of both cold and warm ischemia. Furthermore, the changes in the intestinal mucosa induced by reperfusion injury are noted to begin intraoperatively and vanish within 1 to 2 days after the operation [20]; thus, in this study, we explored the effects of tetrandrine on intestinal reperfusion injury in pigs during the first 24 hours after small bowel transplantation and explored the underlying mechanisms of the actions of the drug. …”
mentioning
confidence: 98%